2012
DOI: 10.1186/1471-2229-12-49
|View full text |Cite
|
Sign up to set email alerts
|

Loss of genetic diversity as a signature of apricot domestication and diffusion into the Mediterranean Basin

Abstract: BackgroundDomestication generally implies a loss of diversity in crop species relative to their wild ancestors because of genetic drift through bottleneck effects. Compared to native Mediterranean fruit species like olive and grape, the loss of genetic diversity is expected to be more substantial for fruit species introduced into Mediterranean areas such as apricot (Prunus armeniaca L.), which was probably primarily domesticated in China. By comparing genetic diversity among regional apricot gene pools in seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
82
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 57 publications
11
82
0
2
Order By: Relevance
“…As a result, local inbreeding coefficients were high in all populations (Table 2). Similar results for cultivated accessions were reported by Dequigiovanni et al (2014) Higher levels of genetic diversity in wild than cultivated crops were also found in other crops, due to genetic bottleneck effects during domestication, such as in tepary beans (Phaseolus acutifolius) (Blair et al 2012, Gujaria-Verma et al 2016 (Bitocchi et al 2013), apricot (Prunus armeniaca) (Bourguiba et al 2012), and sunflower (Helianthus annuus) (Mandel et al 2011). However, this is not always the case, since in some crops, e.g., in carrot (Daucus carota subsp.…”
Section: Resultssupporting
confidence: 58%
“…As a result, local inbreeding coefficients were high in all populations (Table 2). Similar results for cultivated accessions were reported by Dequigiovanni et al (2014) Higher levels of genetic diversity in wild than cultivated crops were also found in other crops, due to genetic bottleneck effects during domestication, such as in tepary beans (Phaseolus acutifolius) (Blair et al 2012, Gujaria-Verma et al 2016 (Bitocchi et al 2013), apricot (Prunus armeniaca) (Bourguiba et al 2012), and sunflower (Helianthus annuus) (Mandel et al 2011). However, this is not always the case, since in some crops, e.g., in carrot (Daucus carota subsp.…”
Section: Resultssupporting
confidence: 58%
“…One of the most important factors in apricot crop evolution was the emergence of self-compatibility, which has resulted in a serious loss of genetic diversity in Europe and the Mediterranean Basin (Pedryc et al, 2009;Bourguiba et al, 2012). In a previous study, Halasz et al (2010) detected an uneven distribution of the S C-allele in Turkish apricot cultivars: no self-compatible cultivar was found among 11 tested genotypes in the Eastern Region, while 7 out of 14 tested cultivars from the Western part of the country were self-compatible.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the different response of ATP levels according to extraction method and validation of ATP measurements with spiking experiments, it can be concluded that there is no single protocol that fits all species or even genotypes, and we conclude that tailor-made protocols are needed in plant metabolomics studies. In response to drought stress, the response level differs among genotypes, highlighting the importance of natural variation in Brachypodium (Opanowicz et al, 2008;Bourguiba et al, 2012;Verelst et al, 2013). This study will provide a basis for the construction of high-coverage metabolome platforms, and potentially lead to more reliable metabolome studies in plants and help further metabolomics studies on drought stress response in order to improve agriculturally important crop species.…”
Section: Discussionmentioning
confidence: 99%